Usefulness of the duration of acute kidney injury for predicting renal function recovery after partial nephrectomy - Kim, Chang Seong; Bae, Eun Hui; Ma, Seong Kwon; Kim, Soo Wan (Annals of Translational Medicine, 2019)
Although the incidence and mortality of renal cell carcinoma (RCC) significantly varies among individual countries, according to the recent GLOBOCAN database, RCC is the sixth most frequently diagnosed cancer in men and the tenth in women worldwide (1,2). The incidence rate of RCC has been increasing in most countries, resulting in more frequent medical examinations and requiring changes to national health insurance policies (3). In addition, with improvement in the resolution of abdominal imaging, such as ultrasonography, computed tomography and magnetic resonance, small renal masses are now found incidentally (4). These small renal masses tend to be localized, with complete surgical excision being the only curative treatment.